People and populism: New perspectives - Ayuso Torres, Miguel (Derecho Público Iberoamericano, 2016)
For understanding contemporary populism it is necessary to consider first the meaning of the ‘people’, sometimes mistaken in modern thinking for nation or third state, differently from classic thinking, characterized by organicity. Populism therefore is not other than a reaction against political liberalism, but influenced more by the same (philosophical) liberalism more than by old marxism.